JDBC Recipes A Problem-Solution Approach - Parsian, Mahmoud; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2005)
JDBC Recipes provides easy-to-implement, usable solutions to problems in relational databases that use JDBC. You will be able to integrate these solutions into your web-based applications, such as Java servlets, JavaServer Pages, and Java server-side frameworks. This handy book allows you to cut and paste the solutions without any code changes. This book focuses on topics that have been ignored in most other JDBC books, such as database and result set metadata. It will help you develop database solutions, like adapters, connectors, and frameworks using Java/JDBC. The insightful solutions will enable you to handle all data types, including large binary objects. A unique feature of the book is that it presents JDBC solutions (result sets) in XML.
Introducing JDBC -- Exploring JDBC’s Novel Feature -- Making Database Connections -- Making Database Connections Using DataSource -- Exploring the ResultSet Interface -- Working with Scrollable and Updatable ResultSet Objects -- Reading and Writing BLOBs -- Reading and Writing CLOBs -- Working with Date, Time, and Timestamp in JDBC -- Handling Exceptions in JDBC -- Exploring the Statement -- Working with the PreparedStatement -- Passing Input Parameters to PreparedStatement -- Exploring JDBC Utilities.
Keywords: Java (Computer program language).; Software engineering; Java; Software Engineering/Programming and Operating Systems